Targeted two-photon chemical apoptotic ablation of defined cell types in vivo - Hill, Robert A. (Nat Commun, 2017)
A major bottleneck limiting understanding of mechanisms and consequences of cell death in complex organisms is the inability to induce and visualize this process with spatial and temporal precision in living animals. Here we report a technique termed two-photon chemical apoptotic targeted ablation (2Phatal) that uses focal illumination with a femtosecond-pulsed laser to bleach a nucleic acid-binding dye causing dose-dependent apoptosis of individual cells without collateral damage. Using 2Phatal, we achieve precise ablation of distinct populations of neurons, glia and pericytes in the mouse brain and in zebrafish. When combined with organelle-targeted fluorescent proteins and biosensors, we uncover previously unrecognized cell-type differences in patterns of apoptosis and associated dynamics of ribosomal disassembly, calcium overload and mitochondrial fission. 2Phatal provides a powerful and rapidly adoptable platform to investigate in vivo functional consequences and neural plasticity following cell death as well as apoptosis, cell clearance and tissue remodelling in diverse organs and species.